2006
DOI: 10.1159/000093248
|View full text |Cite
|
Sign up to set email alerts
|

The Skin Allergenic Properties of Chemicals May Depend on Contaminants – Evidence from Studies on Coumarin

Abstract: Background/Aims: Positive patch tests are considered representative of a contact allergy to the tested chemical. However, contaminants and derivatives rather than the suspected chemical itself could be responsible for the allergic skin reactions. Here, we tested the importance of contaminants in the sensitizing and allergenic properties of coumarin in mice and humans. Coumarin, an ingredient in cosmetics and fragrances, was chosen as the reference chemical since conflicting results have been obtained regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…protective of human health), our reference result was positive. While it was a weak sensitizer in the positive tests (EC3 = 29.6%), the response was attributed to contaminants in commercial products containing coumarin (Vocanson et al , ). For undecylenic acid, both DPRA and KeratinoSens produced correct positive results.…”
Section: Resultsmentioning
confidence: 99%
“…protective of human health), our reference result was positive. While it was a weak sensitizer in the positive tests (EC3 = 29.6%), the response was attributed to contaminants in commercial products containing coumarin (Vocanson et al , ). For undecylenic acid, both DPRA and KeratinoSens produced correct positive results.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, impurities derived from natural products could be allergenic or toxic compounds, which in turn could be the molecular basis of known side effects resulting from counterfeit perfumes. 19,20 The degree of these effects would depend on the 'quality' of a particular counterfeit sample.…”
Section: Resultsmentioning
confidence: 99%
“…DHC, 98% pure and α‐hexylcinnaldehyde (HCA, 85% pure) were purchased from Sigma–Aldrich (Saint Quentin en Fallavier, France). Pure coumarin (Rhodiascent extra pure ® , >99.9% pure) was produced in Rhodia Organics (Lyon, France) (10). All the chemicals were prepared freshly before application, and dissolved in N , N ‐dimethylformamide (DMF; Sigma‐Aldrich, Saint Quentin en Fallavier, France) or in acetone/olive Oil (AOO, Carlos Erba and Lessieur) (4:1, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Because the chemical process of coumarin is critical for the purity of the molecule and because coumarin derivatives and contaminants are endowed with irritant and allergenic properties, we hypothesized that the reported allergenic properties of coumarin could in fact be attributed to contaminants. In a recent study combining murine experiments and human clinical studies, we showed that the coumarin chemical (pure coumarin preparation) was extremely well tolerated (10). In contrast, derivatives contaminating some coumarin preparations were endowed with sensitizing properties detected in the local lymph node assay (LLNA) suggesting that contaminants but not the pure chemical are responsible for both the irritant and sensitizing properties previously attributed to coumarin (10).…”
mentioning
confidence: 98%